Fall History and Associated Physical Performance Measures in Competitive Senior Athletes. Issue 1 (January 2016) - Jordre, Becca; Schweinle, William; Oetjen, Sarah; Dybsetter, Nichole; Braun, Miranda
Abstract : Topic Investigated: Physical performance measure outcomes most associated with falls in senior athletes. Subjects: A total of 928 senior athletes. Variables: Fall history, Single Leg Stance Eyes Open, Single Leg Stance Eyes Closed, Single Leg Stance on Foam, Functional Reach, Usual and Fast Gait Speed, Five Times Sit-to-Stand Test, and Grip Strength. Data were analyzed with logistic regression and receiver operating characteristic curve analyses. Results and Conclusions: Combined failure, as determined by cut scores, on Single Leg Stance Eyes Closed and on Foam was most associated with a recent history of falls. Performance on the Five Times Sit-to-Stand Test was also highly associated.